Doing language im Deutschunterricht. Eine Analyse sprachbezogener Adressierungen in diskursiver Praxis - Büttner, Denise
Die Studie leistet einen empirisch-rekonstruktiven Beitrag zu einer machtkritisch ausgerichteten Fachdidaktik. Sie fokussiert den Deutschunterricht und die darin stattfindenden Interaktionen als diskursive Praxis, in der ein spezifisches Wissen in, über und angesichts von Sprache relevant gemacht wird. Für Subjektivierung ist jenes Wissen hochgradig wirkmächtig und bleibt den Akteur*innen im Prozess der schulischen Enkulturation doch größtenteils unbewusst. Darin liegt ein hohes Potential für die institutionelle (Re-)Produktion von Linguizismus.Vor diesem Hintergrund eröffnet die Studie einen Blick auf sprachbezogene Adressierungen, die in charakteristischer Weise vom Fach selbst ausgehen. Sie werden in (fach)didaktischen und pädagogischen Programmatiken breit kommuniziert und zeichnen sich bis auf die Ebene unterrichtlicher Praktiken ab. Um das Zusammenspiel von fachspezifischer Adressierung und Praktiken des ‚doing language‘ möglichst eng aufeinander beziehen und in rekonstruktionslogisch plausibilisierte Zusammenhänge bringen zu können, liegt der Arbeit ein wissenssoziologisch-diskursanalytischer Ansatz zugrunde.
Keywords: Diskursanalyse; Machtkritik; Sprache und Bildung; Rekonstruktive Unterrichtsforschung; Subjektivierung; Fachdidaktik

Measurement of Ultrashort Biphoton Correlation Times with an Integrated Two-Color Broadband SU(1,1)-Interferometer - Roeder, Franz; Pollmann, René; Stefszky, Michael; Santandrea, Matteo; Luo, Kai Hong; Quiring, V.; Ricken, Raimund; Eigner, Christof; Brecht, Benjamin; Silberhorn, Christine (PRX Quantum)
The biphoton correlation time, a measure for the conditional uncertainty in the temporal arrival of two photons from a photon pair source, is a key performance identifier for many quantum spectroscopy applications, with shorter correlation times typically yielding better performance. Furthermore, it provides fundamental insight into the effects of dispersion on the biphoton state. Here, we show that a characteristic dependence of the width of the temporal interferogram can be exploited to obtain insights into the amount of second-order dispersion inside the interferometer and to retrieve actual and Fourier-limited ultrashort biphoton correlation times of around 100 fs. In the presented scheme, we simultaneously measure spectral and temporal interferograms at the output of an SU(1,1) interferometer based on an integrated broadband parametric down conversion source in a Ti:LiNbO3 waveguide.

§ 6 (Kartellrechtliche Grenzen der Kommanditgesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

§ 78 (Kartellrechtliche Grenzen der stillen Gesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

Immaterielles Kulturerbe und Regionale Identität. Schützenwesen in Nordwestdeutschland

Tailored metrics for assessing the quality of MBSE models - Gräßler, Iris; Wiechel, Dominik; Özcan, Deniz; Taplick, Patrick (Proceedings of the Design Society)
Abstract System models are used to merge relevant engineering artefacts and relationships. Therefore, a high model quality must be ensured. Currently, there is no method for defining company-specific metrics to assess system model quality. In a six-step research approach, a method is defined: (1) literature analysis on quality assessment approaches, (2) derivation of success factors, (3) evaluation of approaches, (4) development of a method, (5) application in automotive industry, and (6) evaluation. The method supports system engineers to derive tailored metrics to objectively assess the model quality.

Young Adult Diaspora Short Stories in the EFL Classroom: Approaching the Country of Reference Nigeria Through the Eyes of Adolescent Narrators - Bauer, Maike (Focus on Reading Young Adult (YA) Literature in the EFL Classroom and Beyond)

Tax Compliance Management Systeme in deutschen Betriebsprüfungen – Eine Analyse praktischer Erfahrungen - Schulz, Kim Alina; Sureth-Sloane, Caren (Steuer und Wirtschaft)

Uncovering Impact of Innovation: Continuous Stakeholder Engagement through Scenario-based Systems Engineering - Pottebaum, Jens; Ebel, Marcel; Gräßler, Iris (Proceedings of the 21st ISCRAM Conference (ISCRAM 2024))
The importance of extreme weather situations is increasing due to their number and, above all, their impact on stakeholders in emergency response. They are characterized by cascading effects with global and local interdependencies. Extreme data must be included as a basis for decision-making. The impact in emergency response depends on diverse, multidisciplinary competencies required to interpret information. Scenarios are used in various forms of preparation: in exercises, but also for the design of information systems and validation. Based on literature, this article brings together different types of scenarios and related work in the field of Model-Based Systems Engineering. Using an exemplary case relating to possible pluvial urban floods, the added value resulting from a focus on the impact of innovative solutions is discussed. It is shown that the use of scenarios helps to make the desired impact assessable for decision-makers in all phases of research and development projects.

Investigation of Fluid Flow and Heat Transfer Characteristics of an Internally Channeled Tube Heat Exchanger under Laminar Flow Conditions - Al-Lami, Abbas Jarullah Sangoor; Kenig, Eugeny Y. (energies)

The Imperative of Revival Strategies through Digital Transformation in the Cultural Sector - A Taxonomy Approach - Althaus, Maike; Hansmeier, Philipp (Proceedings of the Thirty-Second European Conference on Information Systems (ECIS 2024))
Excellent Information Systems (IS) bachelor or master student theses have the potential to inform the scientific community about interesting findings about IS phenomena. However, transforming such theses into scientific working papers is not only time-consuming for the student and the supervisor, but also purely voluntary. Part of the problem is that few IS faculties offer any structured course for the transformation process as part of their curriculum. This significantly reduces the proportion of outstanding theses that are developed into working papers and, ultimately, into publications, resulting in a loss of knowledge for the broader IS community. To address this structural deficit, we aim to develop and implement a credit course and open educational resources (e.g., course schedule, slides, videos) that support students in developing their theses into publishable scientific research papers. This approach not only enriches the scientific discourse but also presents a research-oriented educational disruption for the IS community.
Keywords: Student Thesis; Scientific Publishing; Course Implementation

Erklären ist nicht gleich erklären. Wie erklärt man "gut" im Erklärvideo? - Risse, Sylvia (Praxis Deutsch)

A School Student Essay Corpus for Analyzing Interactions of Argumentative Structure and Quality - Stahl, Maja; Michel, Nadine; Kilsbach, Sebastian; Schmidtke, Julian; Rezat, Sara; Wachsmuth, Henning
Learning argumentative writing is challenging. Besides writing fundamentals such as syntax and grammar, learners must select and arrange argument components meaningfully to create high-quality essays. To support argumentative writing computationally, one step is to mine the argumentative structure. When combined with automatic essay scoring, interactions of the argumentative structure and quality scores can be exploited for comprehensive writing support. Although studies have shown the usefulness of using information about the argumentative structure for essay scoring, no argument mining corpus with ground-truth essay quality annotations has been published yet. Moreover, none of the existing corpora contain essays written by school students specifically. To fill this research gap, we present a German corpus of 1,320 essays from school students of two age groups. Each essay has been manually annotated for argumentative structure and quality on multiple levels of granularity. We propose baseline approaches to argument mining and essay scoring, and we analyze interactions between both tasks, thereby laying the ground for quality-oriented argumentative writing support.
Keywords: Annotation; Corpus; Argumentative Structure

DeepApprox: Rapid Deep Learning based Design Space Exploration of Approximate Circuits via Check-pointing - Awais, Muhammad; Ghasemzadeh Mohammadi, Hassan; Platzner, Marco (To apear in IEEE ISVLSI 2024)

Soziale Grenzen und Grenzbearbeitungen. Ein Zugang zur sozialwissenschaftlichen Bildungsforschung - Haker, Christoph; Otterspeer, Lukas (Bildungsforschung: Erziehungswissenschaftliche Perspektiven)
Der Beitrag führt in die von uns verfolgte Forschungsperspektive der sozialen Grenzen und Grenzbearbeitungen ein und bringt diese mit den Begriffen Bildung und Bildungsforschung zusammen. Unsere Theoretisierung beginnt mit einem sozialtheoretisch unterbestimmten Verständnis sozialer Grenzen und Grenzbearbeitungen. Dieses erhebt einerseits den Anspruch, nah an Alltagserfahrungen mit sozialen Grenzen und Grenzbearbeitungen zu sein. Andererseits ermöglicht es den Einstieg in ganz unterschiedliche Sozialtheorien und damit eine multiperspektivische Forschungspraxis. Dieses Potential plausibilisieren wir am Beispiel von Analysen zu Fragestellungen der Wissenschafts- und Rechtsextremismusforschung, die wir selbst durchgeführt haben. Für Bildung und Bildungsforschung sind in diesem Zusammenhang der Blick auf Bildungsprozesse, Bildungsinstitutionen und die Konzeption von Forschung als eine selbstreflexive Bildungspraxis relevant.

Mit tiergestützter Pädagogik soziale Teilhabe fördern! - Mombeck, Mona Maria

Tiergestützte Pädagogik. Ein Einblick: Grundlagen zum Einsatz von Schulhunden im (inklusiven) Unterricht - Mombeck, Mona Maria
Vortrag LMU München [online]

Asymptotics of extensions of simple $\mathbb Q$-algebras - Gundlach, Fabian; Seguin, Béranger (arXiv:2405.17286)
We answer various questions concerning the distribution of extensions of a given central simple algebra $K$ over a number field. Specifically, we give asymptotics for the count of inner Galois extensions $L|K$ of fixed degree and center with bounded discriminant. We also relate the distribution of outer extensions of $K$ to the distribution of field extensions of its center $Z(K)$. This paper generalizes the study of asymptotics of field extensions to the noncommutative case in an analogous manner to the program initiated by Deschamps and Legrand to extend inverse Galois theory to skew fields.

Nur Provokation oder doch politisches Statement? Der Spot "The Journey" von 84 Lumber aus dem Jahr 2017 - Janus, Richard; Müller, Emma (Weihnachts-Werbespots als moderne Krippenspiele)

Werbung, Krippenspiele und Religion. Einleitende Bemerkungen - Janus, Richard (Weihnachts-Werbespots als moderne Krippenspiele)

Die Sporthalle – Ein Raum zum Sprachenlernen? Zwischen der Forderung nach Integration durch Sport und Sprache(n) als Schlüssel zur Integration - Treder, Alexandra (Transdisziplinäre Räume in den Kultrwissenschaften)

Concepciones de cultura y de encuentros interculturales de futuros/as profesores/as de Alemán como Lengua Extranjera - Treder, Alexandra (Memorias del III Congreso Internacional de Lenguas, Lingüística y Traducción)

Alexandra Treder (Universität Paderborn) rezensiert: Döll, Marion & Michalak, Magdalena (2023): Deutsch als Zweitsprache und inklusive Bildung. [Deutsch als Zweitsprache – Positionen, Perspektiven, Potenziale, Bd. 3]. Münster: Waxmann, 142 Seiten. ISBN 978-3-8309-4711-0. - Treder, Alexandra (Forschungsportal für Spracherwerb und Migration (daz-portal))

Flexible operation and integration of high-temperature heat pumps using large temperature glides - Knorr, Lukas; Schlosser, Florian; Horstmann, Nils; Divkovic, Denis; Meschede, Henning (Applied Energy)

Modular 3D roller straightening – A new approach to straightening and forming of spring steel wires (X10CrNi18-8) - Dahms, Frederik Simon; Homberg, Werner (Materials Research Proceedings)
Abstract. Spring steel wires are usually supplied and stored on coils. The manufacturing and coiling processes of these wires induce inhomogeneous plastic deformations that lead to undesirable residual stresses and varying wire curvatures in the semi-finished product. These residual stresses and curvatures defects are causing varying process conditions in the subsequent manufacturing processes, which have a negative impact on the product quality, leading to wastage and thus affecting the economic and ecological efficiency. Especially the curvature deviations must be compensated for the stability of the subsequent processes. This is usually realised with roller straighteners, which are set manually by the machine operators only at the beginning of a process. In this paper, we introduce a new approach with a modular straightening-machine design and a new set-up process. The more isolated deformation behaviour in a module-based straightener overcomes the complexity of interactions between the close-positioned spaced straightening rollers. This is combined with a set-up process that is independent of conventional material testing, modelling the actual and batch-specific behaviour of the wire in the straightening process. The exact knowledge and time-consuming determination of the material properties thus becomes obsolete. The experimental investigations show the influence of defined straightening strategies on the residual stress evolution and the residual forming limit of the spring steel wires (X10CrNi18-8) in the new straightening process.

The Value of Reputation Systems in Business Contexts – A Qualitative Study Taking the View of Buyers - Hemmrich, Simon; Schäfer, Jannika Marie; Hansmeier, Philipp; Beverungen, Daniel (Proceedings of the 57th Hawaii International Conference on System Sciences (HICSS 2024))

MODELING CUSTOMER JOURNEYS IN DIGITAL DATA ECOSYSTEMS: A DOMAIN-SPECIFIC MODELING LANGUAGE - Hansmeier, Philipp; zur Heiden, Philipp; Beverungen, Daniel (Proceedings of the Thirty-Second European Conference on Information Systems (ECIS 2024))

CONCEPTUALIZING A HYBRID (ONLINE-OFFLINE) EXPERIENCE FRAMEWORK FOR CULTURAL EVENTS - Hansmeier, Philipp; zur Heiden, Philipp (Proceedings of the Thirty-Second European Conference on Information Systems (ECIS 2024))

Blackness in Heiner Müller’s Imaginary - Eke, Norbert (Staging Blackness: Representations of Race in German-Speaking Drama and Theater)

Knowledge Management for Service and Maintenance on the Distribution Grid—Conceptualizing an Assistance System based on a Large Language Model Wissensmanagement für Wartung und Instandhaltung im Verteilnetz – Konzeption eines Assistenzsystems basierend auf einem Large Language Model - zur Heiden, Philipp; Kaltenpoth, Sascha (HMD Praxis der Wirtschaftsinformatik)
Zusammenfassung Verteilnetzbetreiber in Deutschland stehen vor großen Herausforderungen bei dem Management ihres unternehmensspezifischen Wissens: Mitarbeiterengpässe durch den demographischen Wandel, Wissen ist nur implizit vorhanden und nicht in Wissensmanagementsystemen digitalisiert, teilweise gibt es gar keine Wissensmanagementsysteme oder Konzepte und das Verteilnetz wird immer komplexer. Verbunden mit zunehmender Belastung von zentralen Komponenten im Verteilnetz durch die Energiewende bedarf es neuer Lösungen, besonders für die wissensintensiven Wartungs- und Instandhaltungsprozesse. Generative Artificial Intelligence als aufstrebende Technologie, insb. durch Large Language Models, zeigt hier erste Erfolge für die Anleitung, Entscheidungsunterstützung und den Wissenstransfer. Aufbauend auf dem Design Science Research Forschungsparadigma wird in diesem Beitrag ein ganzheitlicher Ansatz des Wissensmanagements konzipiert, welcher als zentrale Komponente auf einem Assistenzsystem basiert. Ein Large Language Model generiert Hilfestellungen für Netzmonteure während der Wartung und Instandhaltung auf Basis von Anleitungen. Neben der Konzeption zeigt dieser Beitrag auch die erarbeitete Strategie zur Demonstration und zukünftigen Evaluation der Ergebnisse. Der Beitrag liefert ein für Verteilnetzbetreiber neuartiges Konzept Large Language Model basierter Assistenzsysteme zum Wissensmanagement und zeigt zudem nachgelagerte Schritte auf, die vor einer Markteinführung notwendig sind.

AFM-IR investigation of thin PECVD SiOx films on a polypropylene substrate in the surface-sensitive mode - Müller, Hendrik; Stadler, Hartmut; de los Arcos, Teresa; Keller, Adrian; Grundmeier, Guido (Beilstein Journal of Nanotechnology)
Thin silicon oxide films deposited on a polypropylene substrate by plasma-enhanced chemical vapor deposition were investigated using atomic force microscopy-based infrared (AFM-IR) nanospectroscopy in contact and surface-sensitive mode. The focus of this work is the comparison of the different measurement methods (i.e., contact mode and surface-sensitive mode) with respect to the chemical surface sensitivity. The use of the surface-sensitive mode in AFM-IR shows an enormous improvement for the analysis of thin films on the IR-active substrate. As a result, in this mode, the signal of the substrate material could be significantly reduced. Even layers that are so thin that they could hardly be measured in the contact mode can be analyzed with the surface-sensitive mode.

Universal Knowledge Graph Embeddings - KOUAGOU, N'Dah Jean; Demir, Caglar; Zahera, Hamada Mohamed Abdelsamee; Wilke, Adrian; Heindorf, Stefan; Li, Jiayi; Ngonga Ngomo, Axel-Cyrille (Companion Proceedings of the ACM on Web Conference 2024)

Utilizing Description Logics for Global Explanations of Heterogeneous Graph Neural Networks - Köhler, Dominik; Heindorf, Stefan (arXiv:2405.12654)
Graph Neural Networks (GNNs) are effective for node classification in graph-structured data, but they lack explainability, especially at the global level. Current research mainly utilizes subgraphs of the input as local explanations or generates new graphs as global explanations. However, these graph-based methods are limited in their ability to explain classes with multiple sufficient explanations. To provide more expressive explanations, we propose utilizing class expressions (CEs) from the field of description logic (DL). Our approach explains heterogeneous graphs with different types of nodes using CEs in the EL description logic. To identify the best explanation among multiple candidate explanations, we employ and compare two different scoring functions: (1) For a given CE, we construct multiple graphs, have the GNN make a prediction for each graph, and aggregate the predicted scores. (2) We score the CE in terms of fidelity, i.e., we compare the predictions of the GNN to the predictions by the CE on a separate validation set. Instead of subgraph-based explanations, we offer CE-based explanations.

Causal Question Answering with Reinforcement Learning - Blübaum, Lukas; Heindorf, Stefan (The World Wide Web Conference (WWW))

Beyond One-Shot Explanations: A Systematic Literature Review of Dialogue-Based XAI Approaches - Mindlin, Dimitry; Beer, Fabian; Sieger, Leonie Nora; Heindorf, Stefan; Cimiano, Philipp; Esposito, Elena; Ngonga-Ngomo, Axel-Cyrille
In the last decade, there has been increasing interest in allowing users to understand how the predictions of machine-learned models come about, thus increasing transparency and empowering users to understand and potentially contest those decisions.Dialogue-based approaches, in contrast to traditional one-shot eXplainable Artificial Intelligence (XAI) methods, facilitate interactive, in-depth exploration through multi-turn dialogues, simulating expert conversations. This paper reviews the current state of dialogue-based XAI, presenting a systematic review of 1,339 publications, narrowed down to 14 based on inclusion criteria. We explore theoretical foundations of the systems, propose key dimensions along which different solutions to dialogue-based XAI differ, and identify key use cases, target audiences, system components, and the types of supported queries and responses. Furthermore, we investigate the current paradigms by which systems are evaluated and highlight their key limitations. Key findings include identifying the main use cases, objectives, and audiences targeted by dialogue-based XAI methods, and summarize the main types of questions and information needs. Beyond discussing avenues for future work, we present a meta-architecture for these systems from existing literature and outlined prevalent theoretical frameworks.

Experimental investigations of uniaxial and biaxial cold stretching within PC‐films and bars using optical measurements - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Abstract Polycarbonate (PC) is an amorphous polymer that is an extremely robust material with a high tenacity, and thus suitable for a lightweight construction with glass‐like transparency. Due to these advantageous properties, PC is often used in industry for example in medical devices, automotive headlamps, sporting equipment, electronics, and a variety of other products. PC is often subjected to uniaxial and biaxial loading conditions. Therefore, reliable material models have to take into account the various resulting experimental effects. For those reasons, we investigate PC specimens under uniaxial and biaxial loading by using different stretch rates and loading scenarios. In addition to that, we propose methods for optical measurement of local stretches to obtain the approximated local true stress. In future work, the displacement fields and the resulting reaction forces will be used for parameter identification of constitutive equations.

Green Multi-Objective Scheduling - A memetic NSGA-III for flexible production with real-time energy cost and emissions - Burmeister, Sascha Christian

Wirtschafts- und Finanzpolitik als Schlüsselbereiche europäischer Einigung - Schönhärl, Korinna; Leucht, Brigitte (Europäische Einigung zwischen Anspruch und Wirklichkeit. Eine historische Bestandsaufnahme)
Im Gespräch loten Brigitte Leucht und Korinna Schönhärl aus, welche Rolle wirtschafts- und finanzpolitische Überlegungen und Faktoren für den europäischen Einigungsprozess gespielt haben und immer noch spielen.
Keywords: Wirtschaftsgeschichte; Europäische Geschichte; Europäische Einigung; Staatsverschuldung; Moderne griechische Geschichte

Sampling cubic rings - Gundlach, Fabian (arXiv:2405.13734)
We explain how to construct a uniformly random cubic integral domain $S$ of given signature with $|\text{disc}(S)| ≤ T$ in expected time $\widetilde O(\log T)$.

“It’s like I got a new pair of glasses”: Reflections on sense of self, home, and belonging among transnational students in short-term study abroad programs - Müller, Mareike (Study Abroad Research in Second Language Acquisition and International Education)
This study focuses on a specific group of sojourners that has thus far remained rather unexplored in the context of study-abroad research, namely, students with extensive prior experiences of living in, traveling to, and/or familial ties with target-language mediated communities. To this end, this study examines data obtained through episodic interviews with three American students, who grew up in close contact with German-speaking communities and studied abroad in Austria for four weeks. By means of thematic analysis, the pre-study abroad sojourn motives and reflections on sense of self, home, and belonging are contrasted with these students’ immediate and delayed post-study abroad accounts. The results shed light on both the challenges young adults grapple with due to their international biographies and the transformative effects students attribute to their short-term sojourns with regard to redefining who they are and what meaning different places of home and heritage have within their individual trajectories.

Security Analysis of BigBlueButton and eduMEET - Heitmann, Nico; Siewert, Hendrik; Moog, Sven; Somorovsky, Juraj (Applied Cryptography and Network Security)
Video conferencing systems have become an indispensable part of our world. Using video conferencing systems implies the expectation that online meetings run as smoothly as in-person meetings. Thus, online meetings need to be just as secure and private as in-person meetings, which are secured against disruptive factors and unauthorized persons by physical access control mechanisms. To show the security dangers of conferencing systems and raise general awareness when using these technologies, we analyze the security of two widely used research and education open-source video conferencing systems: BigBlueButton and eduMEET. Because both systems are very different, we analyzed their architectures, considering the respective components with their main tasks, features, and user roles. In the following systematic security analyses, we found 50 vulnerabilities. These include broken access control, NoSQL injection, and denial of service (DoS). The vulnerabilities have root causes of different natures. While BigBlueButton has a lot of complexity due to many components, eduMEET, which is relatively young, focuses more on features than security. The sheer amount of results and the lack of prior work indicate a research gap that needs to be closed since video conferencing systems continue to play a significant role in research, education, and everyday life.

Repräsentativität und Identität. Die UNESCO-Konvention zum Erhalt des Immateriellen Kulturerbes von 2003 – Entstehung, Umsetzung und Entwicklungen in Deutschland - Seng, Eva- Maria

Zwischen frühneuzeitlicher Idealstadt und den Architektur- und Stadtplanungen der russischen Avantgarde der 1920er Jahre - Seng, Eva- Maria; Saage, Richard (Stadtträume – Traumstädte. Tagungsband der 50. Jahrestagung des Südwestdeutschen Arbeitskreises für Stadtgeschichtsforschung)

, Ideal- und Planstädte im deutschen Südwesten in der Frühen Neuzeit - Seng, Eva- Maria (Stadtträume – Traumstädte. Tagungsband der 50. Jahrestagung des Südwestdeutschen Arbeitskreises für Stadtgeschichtsforschung)

Architektur der Bildungsoffensive. Die NRW-Gesamthochschulen - Seng, Eva- Maria (Junge Hochschulen“ – wissenschafts- und hochschulpolitische Herausforderungen seit der 2. Hälfte des 20. Jahrhunderts)

Protein intake and cancer: an umbrella review of systematic reviews for the evidence-based guideline of the German Nutrition Society - Kühn, Tilman; Kalotai, Nicole; Amini, Anna M.; Haardt, Julia; Lehmann, Andreas; Schmidt, Annemarie; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Lorkowski, Stefan; Louis, Sandrine; et al. (European Journal of Nutrition)
Abstract Purpose It has been proposed that a higher habitual protein intake may increase cancer risk, possibly via upregulated insulin-like growth factor signalling. Since a systematic evaluation of human studies on protein intake and cancer risk based on a standardised assessment of systematic reviews (SRs) is lacking, we carried out an umbrella review of SRs on protein intake in relation to risks of different types of cancer. Methods Following a pre-specified protocol (PROSPERO: CRD42018082395), we retrieved SRs on protein intake and cancer risk published before January 22th 2024, and assessed the methodological quality and outcome-specific certainty of the evidence using a modified version of AMSTAR 2 and NutriGrade, respectively. The overall certainty of evidence was rated according to predefined criteria. Results Ten SRs were identified, of which eight included meta-analyses. Higher total protein intake was not associated with risks of breast, prostate, colorectal, ovarian, or pancreatic cancer incidence. The methodological quality of the included SRs ranged from critically low (kidney cancer), low (pancreatic, ovarian and prostate cancer) and moderate (breast and prostate cancer) to high (colorectal cancer). The outcome-specific certainty of the evidence underlying the reported findings on protein intake and cancer risk ranged from very low (pancreatic, ovarian and prostate cancer) to low (colorectal, ovarian, prostate, and breast cancer). Animal and plant protein intakes were not associated with cancer risks either at a low (breast and prostate cancer) or very low (pancreatic and prostate cancer) outcome-specific certainty of the evidence. Overall, the evidence for the lack of an association between protein intake and (i) colorectal cancer risk and (ii) breast cancer risk was rated as possible . By contrast, the evidence underlying the other reported results was rated as insufficient . Conclusion The present findings suggest that higher total protein intake may not be associated with the risk of colorectal and breast cancer, while conclusions on protein intake in relation to risks of other types of cancer are restricted due to insufficient evidence.

Glycemic response to meals with a high glycemic index differs between morning and evening: a randomized cross-over controlled trial among students with early or late chronotype - Stutz, Bianca; Krueger, Bettina; Goletzke, Janina; Jankovic, Nicole; Alexy, Ute; Herder, Christian; Dierkes, Jutta; Berg-Beckhoff, Gabriele; Jakobsmeyer, Rasmus; Reinsberger, Claus; Buyken, Anette (European Journal of Nutrition)
Abstract Purpose Glycemic response to the same meal depends on daytime and alignment of consumption with the inner clock, which has not been examined by individual chronotype yet. This study examined whether the 2-h postprandial and 24-h glycemic response to a meal with high glycemic index (GI) differ when consumed early or late in the day among students with early or late chronotype. Methods From a screening of 327 students aged 18–25 years, those with early (n = 22) or late (n = 23) chronotype participated in a 7-day randomized controlled cross-over intervention study. After a 3-day observational phase, standardized meals were provided on run-in/washout (days 4 and 6) and intervention (days 5 and 7), on which participants received a high GI meal (GI = 72) in the morning (7 a.m.) or in the evening (8 p.m.). All other meals had a medium GI. Continuous glucose monitoring was used to measure 2-h postprandial and 24-h glycemic responses and their variability. Results Among students with early chronotype 2-h postprandial glucose responses to the high GI meal were higher in the evening than in the morning (iAUC: 234 (± 92) vs. 195 (± 91) (mmol/L) × min, p = 0.042). Likewise, mean and lowest 2-h postprandial glucose values were higher when the high GI meal was consumed in the evening (p < 0.001; p = 0.017). 24-h glycemic responses were similar irrespective of meal time. Participants with late chronotype consuming a high GI meal in the morning or evening showed similar 2-h postprandial (iAUC: 211 (± 110) vs. 207 (± 95) (mmol/L) × min, p = 0.9) and 24-h glycemic responses at both daytimes. Conclusions Diurnal differences in response to a high GI meal are confined to those young adults with early chronotype, whilst those with a late chronotype seem vulnerable to both very early and late high GI meals. Registered at clinicaltrials.gov (NCT04298645; 22/01/2020).

The acute effect of a β-glucan-enriched oat bread on gastric emptying, GLP-1 response, and postprandial glycaemia and insulinemia: a randomised crossover trial in healthy adults - Revheim, Ingrid; Ballance, Simon; Standal, Adelheid Fretland; Rieder, Anne; Dierkes, Jutta; Buyken, Anette; Gilja, Odd Helge; Hausken, Trygve; Rosendahl-Riise, Hanne (Nutrition & Metabolism)
Abstract Background The cereal fibre β-glucan reduces postprandial glycaemia, however, the underlying mechanisms are not fully understood. Thus, the aim of this study was to investigate the acute effect of a β-glucan-enriched oat bread on gastric emptying half-time ( T 1/2 ), gastric emptying lag phase ( T lag ), and gastric emptying rate (GER), and the secretion of glucagon-like peptide-1 (GLP-1) as potential means to influence postprandial glycaemia. Methods A randomised crossover trial was conducted in 22 healthy adults (age 24.6 ± 3.1 years, BMI 23.1 ± 2.7 kg/m 2 ) receiving 25 g available carbohydrates from a β-glucan-enriched oat bread or a control whole-wheat bread at two non-consecutive days. T 1/2 , T lag , and GER were determined based on ultrasound measures of the cross-sectional gastric antrum area in the fasting state and 15, 30, 45, 60, 90, and 120 min postprandially. Capillary glucose, serum insulin, and plasma GLP-1 concentrations were measured at the same time points. Results A biphasic pattern of gastric emptying with a distinct T lag before the commencement of emptying was observed in most subjects for both bread types. While no differences in GER were evident ( p = 0.562), consumption of the oat bread significantly increased T 1/2 by 18 min and T lag by 14 min compared with the whole-wheat bread ( p = 0.005 and p = 0.010, respectively). In addition, the oat bread significantly reduced iAUC 2h for glucose and insulin responses compared with the whole-wheat bread ( p = 0.001 and p < 0.001, respectively). There were no significant differences in GLP-1 response between the two breads ( p = 0.892). Conclusion The increased T 1/2 and T lag could offer a potential mechanism for the observed attenuation of postprandial glycaemia and insulinemia after consumption of the β-glucan-enriched oat bread compared with the whole-wheat bread. Trial registration : The study is registered at clinicaltrails.gov (NCT04571866).

Dietary protein and blood pressure: an umbrella review of systematic reviews and evaluation of the evidence - Boeing, Heiner; Amini, Anna M.; Haardt, Julia; Schmidt, Annemarie; Bischoff-Ferrari, Heike A.; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Lorkowski, Stefan; Louis, Sandrine; Nimptsch, Katharina; et al. (European Journal of Nutrition)
Abstract Introduction This umbrella review aimed to investigate the evidence of an effect of dietary intake of total protein, animal and plant protein on blood pressure (BP), and hypertension (PROSPERO: CRD42018082395). Methods PubMed, Embase and Cochrane Database were systematically searched for systematic reviews (SRs) of prospective studies with or without meta-analysis published between 05/2007 and 10/2022. The methodological quality and outcome-specific certainty of evidence were assessed by the AMSTAR 2 and NutriGrade tools, followed by an assessment of the overall certainty of evidence. SRs investigating specific protein sources are described in this review, but not included in the assessment of the overall certainty of evidence. Results Sixteen SRs were considered eligible for the umbrella review. Ten of the SRs investigated total protein intake, six animal protein, six plant protein and four animal vs. plant protein. The majority of the SRs reported no associations or effects of total, animal and plant protein on BP (all “possible” evidence), whereby the uncertainty regarding the effects on BP was particularly high for plant protein. Two SRs addressing milk-derived protein showed a reduction in BP; in contrast, SRs investigating soy protein found no effect on BP. The outcome-specific certainty of evidence of the SRs was mostly rated as low. Discussion/conclusion This umbrella review showed uncertainties whether there are any effects on BP from the intake of total protein, or animal or plant proteins, specifically. Based on data from two SRs with milk protein, it cannot be excluded that certain types of protein could favourably influence BP.

Nutri-Score 2023 update - Merz, Benedikt; Temme, Elisabeth; Alexiou, Hélène; Beulens, Joline Wilhelma Johanna; Buyken, Anette; Bohn, Torsten; Ducrot, Pauline; Falquet, Marie-Noëlle; Solano, Marta García; Haidar, Hanna; Infanger, Esther; Kühnelt, Charlotte; et al. (Nature Food)